Role of Fasting on Enteroendokrin Cell Remodelling to Prevent Type 2 Diabetes Mellitus - Harapan, Harapan; Fitri Jamil, Kurnia; Hayati, Zinatul; Muhammad, Iqbal (The Journal of The Indonesian Medical Students Association, 2010)
Hitherto, there was no study dedicated to analyze the effect of fasting associated enteroendocrine (EE) cell population remodelling on type 2 diabetes mellitus prevention. This article aimed at discussing the molecular and cellular mechanisms of fasting associated EE cell remodelling to type 2 diabetes mellitus prevention and estimating its effectiveness. It was shown that fasting could inhibit EE cell hyperplasia, thus decreased glucose dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) production from K and L cells. Both hormones caused hyperinsulinemia -via enteroinsular axis- and obesity when they interacted with their respective receptors GIPR and GLP-1R in pancreatic beta cell and adipocyte. This would cause insulin resistance through PI-3 kinase and Cb1. Thus, the levels of GIP and GLP-1 are diabetic predisposition factors. Another study also revealed that EE cell remodelling due to fasting had effective target site on type 2 diabetes mellitus prevention - and was also more superior than GIP and GLP-1 analogs.ÃÂ Key words: type 2 diabetes mellitus, fasting, enteroendocrine cell, GIP, GLP-1